Educational institution administration in Accordance with Good Governance Principles by Administrators of Formal Schools under the Private Education Office of Satun Province - Sammaneah, Hofad; Kheowvongsri, Sajanun (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to explore (1) the level of school administrators’ practices based on good governance principles in formal schools under the Private Education Office of Satun Province, (2) the differences in governance practices classified by type of school, years of experience, and school size, and (3) suggestions for improving governance practices. The research employed a questionnaire with a reliability coefficient of 0.960. Data were analyzed using percentage, mean, standard deviation, t-test, and F-test. The findings revealed that overall and across all dimensions, governance practices were at a high level (Mean = 4.31, S.D. = 0.49). Significant differences were found based on school type (p < .001), while no overall differences were observed based on experience or school size. However, differences based on years of experience were significant in the dimensions of participation and accountability (p < .05). No significant differences were found based on school size. The study recommends that school administrators act as role models in complying with school rules and regulations, carefully plan budget expenditures, and encourage all personnel to understand and responsibly perform their duties.